(untitled) (Proceedings of International Conference on Special Education, 2025)
Children with disabilities in India continue to be excluded from education, with over 27% never attending school and from those who attended, a staggering 12% dropped out (Reddy, 2022; Livewire, 2022). Addressing this gap requires scalable, systemic solutions to empower schools, equip educators, and eliminate social barriers for children with disabilities. This paper presents the Perkins India Model School Program, launched under Project Prayaas in 2023, as a scalable framework for inclusive education embedded within existing school systems (Gleason, Hudson, & Jacobs, 2024; Gloria, Maria 2023 – Perkins School for the Blind). This exploratory paper offers early evidence of potential for transformation on a systemic level while discussing implications for sustainability and further research.